Specific incremental field test for aerobic fitness in tennis. Issue 9 (19th July 2006) - Girard, O; Chevalier, R; Leveque, F; Micallef, J P; Millet, G P
Abstract : Objectives: To compare metabolic and cardiorespiratory responses between subjects undergoing incremental treadmill (non-specific) and tennis field based (sport specific) tests. Methods: Nine junior competitive tennis players randomly performed two incremental protocols to exhaustion: a treadmill test (TT) and a tennis specific fitness test (FT). The FT consisted of repeated displacements replicating the game of tennis at increasing speed on a court. In both tests, ventilatory variables and heart rate (HR) were determined at the ventilatory threshold (VT), respiratory compensation point (RCP), and maximal loads (max). Blood lactate concentration was determined at the point of volitional fatigue. Results: Percentage (mean (SD)) maximal HR (83.6 (5.1) v 83.0 (2.8) and 92.1 (2.1) v 92.3 (2.1)%, respectively) and percentage maximal oxygen uptake (VO2max ) (69.4 (8.1) v 73.5 (6.1) and 84.4 (6.5) v 85.5 (8.7)%, respectively) at the VT and RCP were not different between the FT and TT subjects, whereas VO2max was higher in the FT than in the TT (63.8 (3.0) v 58.9 (5.3) ml/min/kg; p<0.05). Blood lactate concentration (10.7 (3.0) v 10.6 (4.3) mmol/l) did not differ between the TT and FT. Conclusions: Although cardiorespiratory variables were not different at submaximal intensities between the two tests, VO2max values derived from laboratory measurements were underestimated. Using field testing in addition to treadmill testing provides a better measurement of a player's individual fitness level and may be routinely used to accurately prescribe appropriate aerobic exercise training.